Integrating anaerobic co-digestion and BSF larvae cultivation: A sustainable approach to fish innards and food waste management - Nafi'ah, Riris Waladatun; Suhartini, Sri; Hidayat, Nur; Wibisono, Yusuf; Sabrina Sunyoto, Nimas Mayang; Alfisya, Lailia; Wilujeng, Rohmi Nadi; Harahap, Nur Anisah Rizky; Salsabila, Hanna Syakira; Rohma, Novita Ainur; Pratama, Andhika Putra Agus; Md Rezali, Khairil Anas (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
Indonesia produces substantial quantities of organic waste annually, including approximately 2.4 million tons of fish innards from the fisheries sector (in 2023) and 13 million tons of food waste (in 2019). This waste contributes significantly to greenhouse gas emissions, estimated at 1,789.66 kg CO₂-eq per ton of food waste. Addressing this issue requires innovative strategies to reduce emissions and enhance the economic value of organic waste. This study aims to develop and assess an integrated system that combines Anaerobic Co-Digestion (ACoD) and Black Soldier Fly (BSF) larvae cultivation as a sustainable solution for managing fish innards and food waste. The proposed system processes 73,000 kg of organic waste annually, comprising 36,500 kg of fish innards and 32,850 kg of food waste. The ACoD process, utilizing a 10:90 mixing ratio, generates 2,172 m³ of biogas, 41,948.26 kg of digestate, and 14,576.67 kg of residue. Concurrently, BSF larvae cultivation, employing a 40:60 mixing ratio, produces 6,450.29 kg of dried larvae. The integration of ACoD and BSF larvae cultivation provides multiple advantages, including the production of renewable energy, biofertilizers, and high-protein larvae, while reducing organic waste and minimizing environmental impacts. This study demonstrates the potential scalability of the integrated system as a sustainable and economically viable approach to managing fish innards and food waste, contributing to the circular economy and environmental sustainability.